2006
DOI: 10.5979/cha.2006.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Direct Covering Period on the Growth and the Constituents in New Shoots of First Crop of Tea Bush

Abstract: To clarify the effect of covering practice befor tea plucking, the characteristics and the constituents in new shoots of first crop of tea plants were examined with different periods and opening times of direct covering on the bush.The longer period of direct covering brought the decrease of number of new shoots, weight of 100 new shoots, and weight of new shoots. The color of direct-covered-leaves got deeper than without covering at 3-5days after direct covering, and this result became much clearer in 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The SPAD values reached approximately 40 and 50 under open and covering culture respectively during the first cropping season in Y1. These results were similar to those reported by Chutani and Takewaka . By contrast, Inaba et al .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The SPAD values reached approximately 40 and 50 under open and covering culture respectively during the first cropping season in Y1. These results were similar to those reported by Chutani and Takewaka . By contrast, Inaba et al .…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study, 3 epigallocatechin (EGC) contents of new tea shoots became lower with higher shading condition, whereas theanine (Thea) content was higher under shading condition during the first cropping season. Other previous studies [4][5][6] also have reported both decrease in the catechin contents and increase in the amino acid contents under shading culture. For further work, it is necessary to reveal shading intensity effects on the morphological and color traits of new shoots and on the chemical components to understand plasticity of new tea shoot traits to covering culture, because the relations among these traits are considered a trade-off relation called the economics spectrum 12 relating to plant productivity.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The most typical response to shading treatment is the darker green color of leaves owing to increased chlorophyll content (Sano et al, 2018). Previous studies (Chutani and Takewaka, 2006;Kobayashi et al, 2011;Matsunaga et al, 2016;Sano et al, 2018) have additionally revealed that shading treatment causes an increase in the contents of amino acids, especially theanine, and a decrease in the contents of catechins, especially epigallocatechin. The contents of free amino acids and chlorophyll are extremely important determinants of tea quality and price.…”
Section: Introductionmentioning
confidence: 99%